Simulation of Radiation Calculation of Black Body by Using the Interpolation Method - Burhendi, Feli Cianda Adrin; Siswanto, Rizky Dwi; Laksanawati, Wahyu Dian (Omega: Jurnal Fisika dan Pendidikan Fisika, 2019)
Simulation of radiation calculation of black body by using the interpolation method is designed to facilitate the determination of radiation in black matter efficiency. Fortran programming languages are chosen for computational processes. The calculation program that has been designed is able to calculate the efficiency of black body radiation easily and quickly with a fairly small error rate of 0.5%. The light radiation spectrum of objects is around 1000, 1100, 1200, and 1300 $^{°}$C. The $x$ axis shows the wavelength, while the $y$ axis shows the intensity or strength of light. If we pay attention to the curvature of 1000 $^{°}$C, along with the increasing frequency of light, the intensity of light is also getting stronger aka more bright. But at certain light frequencies, the line reaches the peak, and after that the light intensity drops dramatically. At temperatures of 1200 $^{°}$C and 1300 $^{°}$C, even though the temperature rises, the outline of the line graph is similar to the line 1000 $^{°}$C. This is in accordance with the existing theoretical and experimental results.